Pre-fatigue Direct 1RM Testing vs. Post-fatigue Load–Velocity Profiling: Which Better Predicts Maximal Strength in the Deadlift After Resistance Training? - Danica Janicijevic; Deniz Şentürk; Yaodong Gu; Amador García-Ramos (Sports Medicine - Open, 2026)
Abstract Background Resistance training loads are commonly prescribed based on a previously determined 1-repetition maximum (1RM). Whether velocity-based methods better reflect the actual 1RM as fatigue accumulates during the training session than relying on a pre-training 1RM remains unknown. Objectives To determine whether pre-training direct 1RM testing or post-training load–velocity (L–v) profiling more accurately estimates hexagonal barbell deadlift (HBD) 1RM following resistance training-induced fatigue. Methods Twenty-seven resistance-trained males (HBD 1RM = 176.8 ± 20.9 kg) randomly completed three experimental sessions, each involving full incremental loading tests before and after a 30-min intervention: (i) control (rest), (ii) moderate fatigue (5 sets at 70% 1RM performing half the maximal possible repetitions), or (iii) high fatigue (5 sets at 70% 1RM to failure). Post-session 1RM was estimated using six methods: pre-session 1RM, post-session L–v profile, and four velocity-based methods that used the post-session mean velocity (MV) recorded at 50%, 70%, 80%, and 90% 1RM applied to the pre-session %1RM–MV relationship. Each estimate was then compared with the directly measured post-session 1RM. The study was conducted at Istanbul Gelişim University (Istanbul, Türkiye) between 29 March and 26 April 2024. Results The pre-session 1RM (9.5 ± 9.4 kg) and MV50% (− 13.4 ± 13.0 kg) substantially over- and underestimated the actual 1RM, respectively, while smaller errors were observed for the post-session L-v profile (1.9 ± 7.7 kg), MV70% (− 2.8 ± 8.6 kg), MV80% (− 2.5 ± 7.8 kg), and MV90% (− 0.9 ± 5.9 kg). Based on absolute errors, methods were ranked from least to most accurate as: MV50% (15.4 ± 10.5 kg) < pre-session 1RM (9.5 ± 9.4 kg) < MV70% (7.1 ± 5.6 kg) = MV80% (6.5 ± 4.9 kg) = post-session L–v profile (5.9 ± 5.2 kg) < MV90% (4.7 ± 3.7 kg). Notably, pre-session 1RM errors increased with greater fatigue, while those from velocity-based methods remained more stable. Conclusions Reliance on a pre-session 1RM may result in systematic overestimation of relative training loads under resistance training-induced fatigue, whereas velocity-based methods appear to provide more accurate prescriptions of training intensity (%1RM).